Listening Comprehension as a Key Component towards the Success of Foreign Language Learning - KOKROKO, Evans; DUMENYAH, James Kwaku (American Journal of Education and Practice, 2020)
The objective of this article is to clarify the importance of using listening comprehension to facilitate the process of teaching and learning a foreign language. The approaches underlying the trends supporting listening comprehension teaching and learning, coupled with the literature review point to the development of listening skills as a sure way of smooth foreign language learning. The success of developing listening comprehension skills is hedged on involvement of the learner in well thought out activities by the teacher, their effort and practice, as well as the use of ICT. Researchers in the study exhibit components of oral speech communication which provides the basis for development of other speech aspects and cognitive development. Those findings suggest that oral speech communication is a prerequisite for language acquisition